Five minds for the future - Gardner, Howard, 1943- (Boston, Mass. : Harvard Business School Press, 2007)
Argues that the future requires individuals to learn and think in different ways, and defines the cognitive abilities that an individual must master, including the ability to integrate ideas from different disciplines and an appreciation for differences among humans.
Minds viewed globally: a personal introduction -- The disciplined mind -- The synthesizing mind -- The creating mind -- The respectful mind -- The ethical mind -- Conclusion: toward the cultivation of the five minds.
Includes bibliographical references (pages 169-173) and index.
Print version record.
Master record variable field(s) change: 050, 082
Keywords: Multiple intelligences; Social intelligence; Success; Thought and thinking; Success; REFERENCE -- Questions & Answers; Multiple intelligences; Social intelligence; Success; Thought and thinking; Multiple intelligences; Social intelligence; Success; Thought and thinking; Intelligenz; Intelligenzleistung; Sozialkompetenz; Erfolg; Leiderschap; Cognitieve vaardigheden; Intelligenzleistung; Sozialkompetenz; Erfolg; Multipla intelligenser; Medvetandefilosofi; Social kompetens; Framgång; Tänkande; Kognition; Lernpsychologie; Kreativität; elektronické knihy; electronic books